Influence of Rootstocks on Photosynthesis in Navel Orange Leaves: Effects on Growth, Yield, and Carbohydrate Distribution - Jover, Sara; Martínez-Alcántara, Belén; Rodriguez-Gamir, Juan; Legaz, Francisco; Primo-Millo, Eduardo; Forner Valero, Juan B.; Forner-Giner, María A. (2017)
The effects of two rootstocks on tree growth, fruit set and development, yield, CO2 assimilation, C-13-photoassimilates transport, and carbohydrate distribution were investigated. Cleopatra mandarin (CM) (Citrus reshni hort. ex Tanaka) and Forner-Alcaide 13 (FA-13) [Citrus reshni hort. ex Tanaka x Poncirus trifoliata (L.) Rat] rootstocks were used for this study. The first experiment was performed with 2-yr-old plants grown under greenhouse conditions. The results showed that leaves from navel orange [Citrus sinensis (L.) Osbeck] grafted onto FA-13 rootstock (navel onto FA-13) had higher net CO2 assimilation (Aco(2)) rates than those from navel orange grafted onto CM rootstock (navel onto CM). Also, FA-13 rootstock induced an increase in leaf transpiration rate with respect to CM rootstock resulting in similar water use efficiency (WUE) values. The higher of photosynthetic activity in navel onto FA-13 plants resulted in higher photoassimilate transport (C-13-labeled) from leaves to roots compared to navel onto CM plants, causing higher sucrose and starch accumulation in FA-13 roots. The second experiment was performed under field conditions using 7-yr-old trees. Navel orange grafted onto FA-13, which had the highest Aco(2) values, displayed higher photoassimilate transport (13C-labeled) from leaves to developing fruits than those on CM. navel onto FA-13 leaf sucrose content decreased compared to navel onto CM and leaf concentrations of this sugar were inversely correlated with Aco(2) values. On the other hand, sucrose and starch concentrations in root bark appeared to be related with fruit sink strength. In conclusion, FA-13 rootstock enhances photosynthetic rate in navel orange leaves compared to CM and differences in this parameter affected growth and increased yield.